2013
DOI: 10.7860/jcdr/2013/5552.3281
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Oral Squamous Cell Carcinoma ( O SCC ) – Role of Genetics: A Literature Review

Abstract: According to GLOBOCAN 2008, there were 12.7 million new cancer cases and 7.6 million deaths. Among these, 56% of the cases and 64% of the deaths occurred in the economically developing world. Oral cancer accounted for 3-4% of all cancers. There were 263,900 oral cancer cases, with almost two-thirds of them occurring in men. Oral cancer is among the leading cancer types in south central Asian men. In India, oral cancer is the leading cancer type among men and third most common cancer among women [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[3][4][5] Currently practiced screening/diagnostic tools suffer from several disadvantages like tedious sample preparation, long output times, and interobserver variances. 6,7 Biopsy followed by histopathology, the current gold standard, is not only invasive but also depends on selection of appropriate region. Further, it may not be very convenient for screening and therapeutic monitoring which require repeated sampling.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Currently practiced screening/diagnostic tools suffer from several disadvantages like tedious sample preparation, long output times, and interobserver variances. 6,7 Biopsy followed by histopathology, the current gold standard, is not only invasive but also depends on selection of appropriate region. Further, it may not be very convenient for screening and therapeutic monitoring which require repeated sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Thorough examination and appropriate selection of biopsy sites, coupled with expert histopathologic evaluation, are required for diagnosis of oral leukoplakia and erythroplakia [21]. Analysis of correlations between biomarkers, stages of dysplasia and their progression to OSCC is complex and it requires incorporation of multiple variables [22] In our study, it has been revealed that the keratinizing SCC, unlike the non-keratinizing counterpart presents with pleomorphic, highly keratinized squamous cells. These cells vary greatly in size and shape and tend to occur singly with few small groups or syncytial arrangements.…”
Section: Discussionmentioning
confidence: 84%
“…The detection of OSCC in the early stages is difficult, as most of the cases are asymptomatic and, by clinical examination, look similar to PMOLs such as leukoplakia, erythroplakia or OLP [ 109 , 110 ]. Moreover, the distinction between different types of PMOLs is difficult, and from a clinical point of view, the majority of cases will have an imprecise diagnosis [ 111 ].…”
Section: Difficulties Associated With the Early Diagnosis Of Osccmentioning
confidence: 99%